Pedagogical diagnosis as a form of support for school students in the wake of the pandemic - Justyna Nowotniak (Studia z Teorii Wychowania)
This article presents a fragment of results of a research - its subject being “Diagnosing needs and expectations of students and teachers in primary schools in Szczecin days before returning to school” - conducted in May 2021 among 1125 students. Comfort-Stretch-Panic model, created by Karl Rohnke, has been used as a theoretical framework for said research. It has been shown that 18.6% of students function in high-to-extremely-high levels of panic, thus require aid - with 1 in 4 students stating that they can not receive such aid from their parents. Monitoring these children’s situation requires further systematic, multifaceted diagnosis.Given problem acts as a starting point towards discussion regarding the quality of pedagogical diagnosis in contemporary school, as well as means of its further improvement.